ULTRAHIGH PRESSURE METAMORPHIC ROCKS FROM THE CHINESE CONTINENTAL SCIENTIFIC DRILLING PROJECT: I. PETROLOGY AND GEOCHEMISTRY OF THE MAIN HOLE (0–2,050 M) - Zhang Z.; Xiao Y.; Hoefs J.; Liou J.G.; Simon K. (My University, 2006)
The main hole (MH) of the Chinese Continental Scientific Drilling Project (CCSD) in southern Sulu has penetrated into an ultrahigh-pressure (UHP) metamorphic rock slice which consists of orthogneiss, paragneiss, eclogite, ultramafic rock and minor schist. Recovered eclogites have a UHP metamorphic mineral assemblage of garnet + omphacite + rutile ± phengite ± kyanite ± coesite ± epidote. Ultramafic rocks contain garnet + olivine + clinopyroxene + orthopyroxene ± Ti-clinohumite ± phlogopite. Gneisses and schists contain an amphibolite-facies paragenesis, but their zircons have coesite, garnet, omphacite (or jadeite) and phengite inclusions, indicating that eclogites and gneisses have been subjected to in situ UHP metamorphism. Using available geothermobarometers, P–T estimates of 3.1–4.4 GPa and 678–816°C for eclogites were obtained. If surface outcrops and neighboring shallow drill holes are considered together, we suggest that a huge supracrustal rock slab (> 50 km long  ×  100 km wide  ×  5 km deep) was subducted to a depth >  100 km and then exhumed to the surface. The depth interval (0–2,050 m) of the CCSD-MH can be divided into six lithological units. Unit 1 consists of alternating layers of quartz-rich and rutile-rich eclogites, with thin interlayers of gneiss and schist. Eclogites of unit 1 are characterized by Nb, Ta, Sr and Ti depletions, low Mg number and general LREE enrichment. Unit 2 comprises rutile- and ilmenite-rich eclogite and minor “normal” eclogite and is characterized by high TiO2, total Fe, V, Co and Sr, and very low SiO2, alkali, Zr, Ba, Nb, Ta and total REE contents, and LREE-depleted REE patterns with slightly positive Eu anomalies. Unit 3 contains ultramafic rock and minor MgO-rich eclogite. Protoliths of UHP rocks from units 1, 2 and 3 represent a layered mafic to ultramafic intrusion at crustal depth. Units 4 and 6 consist of interlayered eclogite and paragneiss; the eclogites are characterized by Th, U, Nb, Ta and Ti depletion and K enrichment and LREE-enriched REE patterns. Paragneisses show Nb, Ta, Sr and Ti depletions and LREE-enriched REE patterns occasionally with slightly negative Eu anomalies, indicating that their protoliths represent metamorphic supracrustal series. Unit 5 consists mainly of orthogneisses, showing distinct Nb, Ta, Sr and Ti depletions, and LREE-enriched REE patterns with pronounced negative Eu anomalies, suggesting granitic protoliths. In conclusion it is proposed that the southern Sulu UHP belt consists of a series of meta-supracrustal rocks, a layered mafic–ultramafic complex and granites.
Keywords: KYANITE; ULTRAMAFIC ROCK; GARNET PERIDOTITE; RARE EARTH ELEMENT PATTERN; RARE EARTH ELEMENT